2022
DOI: 10.1101/2022.06.28.22277025
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification and characterization of genetic risk shared across 24 chronic pain conditions in the UK Biobank

Abstract: Chronic pain is attributable to both local and systemic pathology. To investigate the latter, we focused on genetic risk shared among 24 chronic pain conditions in the UK Biobank. We conducted genome-wide association studies (GWAS) on all conditions and estimated genetic correlations among them, using these to model a factor structure in Genomic SEM. This revealed a general factor explaining most of the shared genetic variance in all conditions and an additional musculoskeletal pain-selective factor. Network a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 148 publications
0
15
0
Order By: Relevance
“…The Task Force for the Classification of Chronic Pain recommended that chronic pain conditions be classified based on their etiology ( i.e., visceral pain), underlying pathophysiology ( i.e., neuropathic pain), or body site ( i.e., knee pain) 16, 17 . Despite notable differences between these conditions, the evidence also suggests that different pain conditions are overlapping with one another 19 , sharing a common genetic risk factor 20, 21 , and showing similar alterations in the central nervous system 13, 22, 23 . Thus, different conditions share common risk factors and primary chronic pain has been recognized as a disease on its own term rather than the symptom of another disease 18 .…”
mentioning
confidence: 99%
“…The Task Force for the Classification of Chronic Pain recommended that chronic pain conditions be classified based on their etiology ( i.e., visceral pain), underlying pathophysiology ( i.e., neuropathic pain), or body site ( i.e., knee pain) 16, 17 . Despite notable differences between these conditions, the evidence also suggests that different pain conditions are overlapping with one another 19 , sharing a common genetic risk factor 20, 21 , and showing similar alterations in the central nervous system 13, 22, 23 . Thus, different conditions share common risk factors and primary chronic pain has been recognized as a disease on its own term rather than the symptom of another disease 18 .…”
mentioning
confidence: 99%
“…Secondly, combining the protein interaction data, we identified 24 conservative KDs shared by NP and IP in multiple tissues. Recent studies have found that genetic factors in pain susceptibility [ 58 ] and shared across chronic pain conditions [ 59 ] act through mechanisms within the brain. Remarkably, we revealed that the KDs shared by NP and IP are mainly expressed in the amygdala, caudate nucleus, caudate putamen, cerebellum, frontal lobe, hippocampus, substantia nigra, and other brain tissues ( Table 1 ), which echoes the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has revealed dual neuronal and immunological etiology for pain susceptibility using GWAS meta-analysis [ 58 ]. Interestingly, although another study reported no association between chronic pain and inflammatory cytokines [ 59 ], substantial evidence has linked inflammation and the immune system to multiple chronic pain conditions [ 65 , 66 ]. Consistent with Evelina Mocci et al’s analysis [ 58 ], we further highlight the role of regulation in the immune system and neuronal function shared by NP and IP.…”
Section: Discussionmentioning
confidence: 99%
“…There are also signi cant genetic correlations between pain phenotypes and psychiatric, substance use, cognitive, anthropometric, and circadian traits 21,[23][24][25]29,34 . This shared genetic predisposition suggests that a common genetic susceptibility underlies a broad range of diverse chronic pain conditions 34 and common co-occurring conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There are also signi cant genetic correlations between pain phenotypes and psychiatric, substance use, cognitive, anthropometric, and circadian traits 21,[23][24][25]29,34 . This shared genetic predisposition suggests that a common genetic susceptibility underlies a broad range of diverse chronic pain conditions 34 and common co-occurring conditions. For example, Mendelian randomization (MR) and latent causal variable analyses have shown positive causal effects of speci c bodily site pain on depression 35,36 and bi-directional casual associations between multisite chronic pain and major depressive disorder (MDD) 25,35 .…”
Section: Introductionmentioning
confidence: 99%